Microsurgical Clipping of Ruptured Distal Posterior Inferior Cerebellar Artery Aneurysm: 3-Dimensional Operative Video. Issue 2 (18th June 2018) - Wainberg, Ricardo Chmelnitsky; da Costa, Marcos Devanir Silva; Hernández, Yair A Ugalde; Caramanti, Ricardo Lourenço; Alves Filho, César Augusto Ferreira; Palmiero, Helbert; Saick, Ricardo Pagung; Chaddad-Neto, Feres
Abstract: The distal posterior inferior cerebellar artery (PICA) is a rare site of aneurysm formation. Only small case series and case reports regarding surgical treatment are found in the literature. The PICA is divided into 5 segments (anterior medullary, lateral medullary, tonsilomedullary, telovelotonsillary, and cortical), and the distal ones represent the most complex, due to anatomic variations. We present a case of a 69-yr-old female patient who has suffered from a sudden and intense occipital headache, associated with nausea and vomiting. CT scan showed intraventricular hemorrhage, and further investigation with MRI and MR Angiography revealed a small distal PICA aneurysm, at the superior part of the medial aspect of the left cerebellar tonsil. Digital angiography has demonstrated the aneurysm at the tonsilomedullary segment of the PICA. In this 3-dimensional video, the authors show the microsurgical clipping of a saccular distal PICA aneurysm in the close relation to a choroidal branch, performed by median suboccipital craniotomy. Step-by-step of the dissection, relevant surrounding anatomy and aneurysm clipping is demonstrated. The patient signed the Institutional Consent Form, which allows the use of his/her images and videos for any type of medical publications in conferences and/or scientific articles.